2008
DOI: 10.1097/wco.0b013e328305bdaf
|View full text |Cite
|
Sign up to set email alerts
|

Gait disorders and balance disturbances in Parkinsonʼs disease: clinical update and pathophysiology

Abstract: Insights into the pathophysiology of Parkinson's disease continue to grow. At the same time, it is becoming clear that some patients may in fact deteriorate with treatment. Future research should focus on the development and evaluation of multifactorial fall prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
174
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(197 citation statements)
references
References 85 publications
12
174
0
11
Order By: Relevance
“…Consistent with previous research, 3,4,7 it confirms that they fall frequently. This program it has shown that attendance at CBC was effective in improving some aspects of dynamic balance in the target population, as measured by the Step Test.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with previous research, 3,4,7 it confirms that they fall frequently. This program it has shown that attendance at CBC was effective in improving some aspects of dynamic balance in the target population, as measured by the Step Test.…”
Section: Discussionsupporting
confidence: 80%
“…3,4 There are also a range of non-motor features of PD, including autonomic dysfunction, neuropsychiatric disturbance and cognitive impairment, which may further contribute to the risk of falling. 4 Falls and fractures have been well documented to cause significant morbidity 5 and mortality 6 in older people and have been shown to be the most common reason for patients with PD to require admission to hospital. 7 Poor Imbalance is also an independent risk factor for admission to a nursing home for patients with PD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postural instability, which increases with duration and severity of the disease including gait disorders, balance impairments with subsequent falls and fall-related injuries affects the quality of life negatively [4,7]. The cardinal features of PD are rest tremor, rigidity and bradykinesia; disease-specific features include stooped posture, slow movements, trunk imbalance with shuffling gait, and expressionless facies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Postural instability (PI) is known to be a levodopa-resistant characteristic of advanced idiopathic Parkinson's disease (IPD) that worsens with disease progression [1][2][3]. High frequency deep brain stimulation of the globus pallidus internus (GPI-DBS) has been shown to elicit significant anti-parkinsonian effects superior to best medical therapy reducing tremor, bradykinesia and rigidity, and suppressing levodopa-induced dyskinesias [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%